Audit Quality and its Effect on the Financial Performance of the Firm: A Case Study of Pakistan - Muhammad Naveed Javed; Ashfaq Ahmad; Asad Iqbal; Waseem Qadri (Manunggal Halim Jaya, 2026)
The paper investigates the role of audit committee characteristics in a firm's financial performance. During the ongoing economic recession and the world financial crisis, the corporate governance systems are quite notorious. The audit committee represents one of the most important aspects of efficient corporate governance in companies. In Pakistan, little evidence exists on the effects of audit committees and their attributes on firm performance in the Pakistani literature. Four key characteristics of the audit committee were defined to examine their influence on the company's financial performance: independence, activity, size, and quality of the external audit. The researchers used Tobin's Q to quantify the market and ROA to quantify the accounting business. The panel data analysis showed that the size of the audit committee and the quality of the external audit positively and statistically significantly affect Return on Assets (ROA) and Tobin's Q. Two more variables, including audit committee independence and AC activity, also do not lead to any significant effect, and this can also be seen through the results of the jurisdiction studies that have been conducted in different countries. Essentially, the study has provided valuable information to regulators, policymakers, and stakeholders in Pakistan regarding the adoption of specific audit committee qualities. Incorporating these qualities can improve firms' financial performance. To determine whether the corporation's performance has improved, the audit committee's skills can be used to gather information at the company's administrative level.